Interferon-regulatory factor 4 is essential for the developmental program of T helper 9 cells - Staudt, Valérie; Bothur, Evita; Klein, Matthias; Lingnau, Karen; Reuter, Sebastian; Grebe, Nadine; Gerlitzki, Bastian; Hoffmann, Markus; Ulges, Alexander; Taube, Christian; Dehzad, Nina; Becker, Marc; et al. (Immunity, 2010)
Interferon-regulatory factor 4 (IRF4) is essential for the development of T helper 2 (Th2) and Th17 cells. Herein, we report that IRF4 is also crucial for the development and function of an interleukin-9 (IL-9)-producing CD4(+) T cell subset designated Th9. IRF4-deficient CD4(+) T cells failed to develop into IL-9-producing Th9 cells, and IRF4-specific siRNA inhibited IL-9 production in wild-type CD4(+) T cells. Chromatin-immunoprecipitation (ChIP) analyses revealed direct IRF4 binding to the Il9 promoter in Th9 cells. In a Th9-dependent asthma model, neutralization of IL-9 substantially ameliorated asthma symptoms. The relevance of these findings is emphasized by the fact that the induction of IL-9 production also occurs in human CD4(+) T cells accompanied by the upregulation of IRF4. Our data clearly demonstrate the central function of IRF4 in the development of Th9 cells and underline the contribution of this T helper cell subset to the pathogenesis of asthma.